2021
DOI: 10.1155/2021/5519587
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone Ameliorates Senescence and Calcification by Modulating Autophagy in Rat Tendon‐Derived Stem Cells via the NF‐κB/MAPK Pathway

Abstract: Tendinopathy is a disabling musculoskeletal disease, the pathological process of which is tightly associated with inflammation. Spironolactone (SP) has been widely used as a diuretic in clinical practice. Recently, SP has shown anti-inflammatory features in several diseases. Tendon-derived stem cells (TDSCs), a subset cell type from tendon tissue possessing clonogenic capacity, play a vital role in the pathological process of tendinopathy. In the present study, the protective effect of SP on TDSCs was demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…[ 15 ] Recently, studies have observed that NF‐κB was activated in senescent TSPCs, which could contribute to the hypofunction of AT‐SCs. [ 16 ] Therefore, we explored whether SHED‐Exo bio‐nanoparticles could curb the activation of the NF‐κB signaling pathway. Treatment with SHED‐Exos in vitro inhibited the phosphorylation of p65 and nuclear translocation of p65 in AT‐SCs (Figure S3a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 15 ] Recently, studies have observed that NF‐κB was activated in senescent TSPCs, which could contribute to the hypofunction of AT‐SCs. [ 16 ] Therefore, we explored whether SHED‐Exo bio‐nanoparticles could curb the activation of the NF‐κB signaling pathway. Treatment with SHED‐Exos in vitro inhibited the phosphorylation of p65 and nuclear translocation of p65 in AT‐SCs (Figure S3a,b, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB , which has already been shown to play a role in inflammation, is activated by pro-inflammatory cytokines, including TNFα and IFNγ. NF-κB expression is also dependent on IRF1 activation, and increased NF - κ B levels are detected in early RC tendinopathy [ 33 , 34 , 35 , 36 ]. In our study, NF - κ B was not significantly modulated by TNFα and IFNγ cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The senescence detected assay was conducted as previously described (Xu et al, 2021). Briefly, pretreated chondrocytes in 12-well plates were incubated with β-Galactosidase staining buffer for 24 h from β-Galactosidase activity assay (C0602, Beyotime Biotechnology, China) according to the manufacturer's instructions.…”
Section: β-Galactosidase Activity Assaymentioning
confidence: 99%
“…To further elucidate the underlying mechanism of NitC on RACs, several emerging bioinformatics were performed as our previous study (Xu et al, 2021). To begin with, PharmMapper was used to predict the potential protein targets directly binding with NitC.…”
Section: Nitc Was Capable Of Inhibiting Ros Generationmentioning
confidence: 99%